Prevalence and changing antimicrobial resistance profiles of Shigella spp. isolated from diarrheal patients in Kolkata during 2011-2019. - Puja Bose; Goutam Chowdhury; Gourab Halder; Debjani Ghosh; Alok K Deb; Kei Kitahara; Shin-Ichi Miyoshi; Masatomo Morita; Thandavarayan Ramamurthy; Shanta Dutta; Asish Kumar Mukhopadhyay (Public Library of Science (PLoS), 2024)
Background The primary aim of this study was to investigate the occurrence, characteristics, and antimicrobial resistance patterns of various Shigella serogroups isolated from patients with acute diarrhea of the Infectious Diseases Hospital in Kolkata from 2011-2019. Principal findings During the study period, Shigella isolates were tested for their serogroups, antibiotic resistance pattern and virulence gene profiles. A total of 5.8% of Shigella spp. were isolated, among which S. flexneri (76.1%) was the highest, followed by S. sonnei (18.7%), S. boydii (3.4%), and S. dysenteriae (1.8%). Antimicrobial resistance against nalidixic acid was higher in almost all the Shigella isolates, while the resistance to β-lactamases, fluoroquinolones, tetracycline, and chloramphenicol diverged. The occurrence of multidrug resistance was found to be linked with various genes encoding drug-resistance, multiple mutations in the topoisomerase genes, and mobile genetic elements. All the isolates were positive for the invasion plasmid antigen H gene (ipaH). Dendrogram analysis of the plasmid and pulsed-field electrophoresis (PFGE) profiles revealed 70-80% clonal similarity among each Shigella serotype. Conclusion This comprehensive long-term surveillance report highlights the clonal diversity of clinical Shigella strains circulating in Kolkata, India, and shows alarming resistance trends towards recommended antibiotics. The elucidation of this study's outcome is helpful not only in identifying emerging antimicrobial resistance patterns of Shigella spp. but also in developing treatment guidelines appropriate for this region.